Students’ Perception of Using Zoom Meeting for English Microteaching Class - Cindy Aulia Afrijon; Nur Rosita (Universitas Negeri Padang, 2022)
The process of changing learning produces a variety of different views. This study aims to reveal students' perceptions of using the zoom meeting application for online microteaching classes through pedagogical, socio-cultural, and technical aspects. The population in this study were twenty (20) 3rd-year students of the English education study program who had attended microteaching classes and of course were able to provide their views and opinions. It can be concluded that students have a relatively positive perception of using the zoom meeting application for online microteaching class. The results of the study represent the positive result in carrying out microteaching lectures online. Even though the lectures are conducted online, they lecture still runs according to the standard. For interactive learning applications that are used, students seem happy to use the Zoom Meeting application as a learning medium because apart from being practical and simple, zoom meetings also rarely cause problems that are difficult to handle.